Nurnus monastery and its excavations - Grigoryan, Avetis; Ghulyan, Artak; Simonyan, Hasmik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
Nurnus Monastery is located on the western side of Nurnus village of Byureghavan community in Kotayk Region of the Republic of Armenia, on the left bank of the Hrazdan River gorge. The main structure of the monastery, St. Astvatsatsin, is a partially destroyed church. The exact date of construction is unknown, but according to the architectural composition and interior features, it can be dated to the second half of the 13th century. A courtyard was attached to the western side of the church in a later period, where only the lower rows of walls have been preserved. The medieval cemetery spreads around the church and courtyard. The sacred landscape of the Nurnus Monastery likely included St. Astvatsatsin Church, 3 more churches located in a distance of 200 m and the rich graveyards with khachkars (cross-stones) and tombstones spread around them. The information preserved in original sources, particularly in Armenian manuscripts, show that in the 14-17th centuries Nurnus Monastery was an important center of writing. The three dated inscriptions found in the monastery also refer to the same period. In order to restore the St. Astvatsatsin Church of Nurnus Monastery and put in order the environment excavations were carried out in 2022. The unearthed artefacts mainly refer to the 13-17th centuries, while the area of the church has been inhabited since prehistoric times as evidenced by the lithic tools dating to the Paleolithic period.